Parenting Studies by an Ecocultural and Transactional Perspective - Benedetto, Loredana; Ingrassia, Massimo (IntechOpen, 2021)
Along with development, parents and children are involved in reciprocal exchanges within which both co-adapt their emerging relationships. With this transactional assumption, the eco-cultural approach stimulates researchers to study parenting from a complex perspective and to consider multiple influences shaping children's and families' lives. This book offers a wide, concrete eco-cultural perspective on parenting, addressing current issues such as wellbeing and emotional security, sibling relationships, vulnerable children, family-school partnerships, digital parenting, adolescence and risks, resilience in adversity, and immigration and cultural diversity. Written by researchers from all over the world, the twelve chapters in this volume testify to the strength of the plurality method for approaching parenting.